1991
DOI: 10.1002/jcp.1041460110
|View full text |Cite
|
Sign up to set email alerts
|

Programmed cell death (apoptosis) is induced rapidly and with positive cooperativity by activation of cyclic adenosine monophosphate‐kinase I in a myeloid leukemia cell line

Abstract: Programmed death (apoptosis) of the rat myelocytic leukemic cell line IPC-81 was triggered by cyclic adenosine monophosphate (cAMP) analogs or by agents (cholera toxin, prostaglandins) increasing the endogenous cAMP level. The induction of cell death by cholera toxin was preceded by increased activation of cAMP-kinase. Cell lysis started already 5 hr after cAMP challenge and was preceded by internucleosomal DNA fragmentation and morphological changes characteristic of apoptosis. The cell suicide could be preve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
60
1
1

Year Published

1992
1992
1997
1997

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 123 publications
(65 citation statements)
references
References 42 publications
(37 reference statements)
3
60
1
1
Order By: Relevance
“…Furthermore, cell death is delayed by treating IPC-81 cells with actinomycin D or cycloheximide. This treatment suppresses morphological changes typical of apoptosis, as well as DNA fragmentation and 28S rRNA cleavage (Lanotte et al, 1991;Houge et al, 1993Houge et al, , 1995. This suggest a direct involvement of PKA-directed gene expression.…”
Section: Introductionmentioning
confidence: 75%
See 4 more Smart Citations
“…Furthermore, cell death is delayed by treating IPC-81 cells with actinomycin D or cycloheximide. This treatment suppresses morphological changes typical of apoptosis, as well as DNA fragmentation and 28S rRNA cleavage (Lanotte et al, 1991;Houge et al, 1993Houge et al, , 1995. This suggest a direct involvement of PKA-directed gene expression.…”
Section: Introductionmentioning
confidence: 75%
“…We have previously shown that agonistic stimulation of adenylate cyclase coupled membrane receptors or treatment with cholera toxin and cAMP analogues induce IPC-81 cells to undergo apoptosis (Lanotte et al, 1991).…”
Section: Prostaglandin Treatment Induces Apoptosis Of Ipc-81 Cellsmentioning
confidence: 99%
See 3 more Smart Citations